2014
DOI: 10.1152/japplphysiol.00334.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voluntary hypocapnic hyperventilation on the relationship between core temperature and heat loss responses in exercising humans

Abstract: Two thermolytic thermoregulatory responses, cutaneous vasodilation and sweating, begin when core temperature reaches a critical threshold, after which response magnitudes increase linearly with increasing core temperature; thus the slope indicates response sensitivity. We evaluated the influence of hypocapnia induced by voluntary hyperventilation on the core temperature threshold and sensitivity of thermoregulatory responses. Ten healthy males performed 15 min of cycling at 117 W (29.5°C, 50% RH) under three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
(82 reference statements)
2
12
0
Order By: Relevance
“…There has been little research into the interaction between chemoreceptors and thermoreceptors. In resting humans, hypocapnia achieved through voluntary hyperventilation reduces cutaneous blood flow elicited by moderate heat stress in nonglabrous skin and in exercising humans, hypocapnia induced by voluntary hyperventilation attenuates cutaneous vasodilatory responses by increasing the vasodilatory threshold and reducing sensitivity . In contrast, hypercapnia causes modest vasodilation in nonglabrous skin under normothermic conditions, whereas superimposed hypercapnia during passive heating does not affect cutaneous blood flow .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There has been little research into the interaction between chemoreceptors and thermoreceptors. In resting humans, hypocapnia achieved through voluntary hyperventilation reduces cutaneous blood flow elicited by moderate heat stress in nonglabrous skin and in exercising humans, hypocapnia induced by voluntary hyperventilation attenuates cutaneous vasodilatory responses by increasing the vasodilatory threshold and reducing sensitivity . In contrast, hypercapnia causes modest vasodilation in nonglabrous skin under normothermic conditions, whereas superimposed hypercapnia during passive heating does not affect cutaneous blood flow .…”
Section: Discussionmentioning
confidence: 97%
“…In resting humans, hypocapnia achieved through voluntary hyperventilation reduces cutaneous blood flow elicited by moderate heat stress in nonglabrous skin 36 and in exercising humans, hypocapnia induced by voluntary hyperventilation attenuates cutaneous vasodilatory responses by increasing the vasodilatory threshold and reducing sensitivity. 37 In contrast, hypercapnia causes modest vasodilation in nonglabrous skin under normothermic conditions, 10 whereas superimposed hypercapnia during passive heating does not affect cutaneous blood flow. 38 Overall, these findings suggest that hypocapnia might contribute to the blunted forearm cutaneous blood flow responses to heating during hypoxia, but further examination of the cutaneous vascular responses to hypoxia with and without the attendant hypocapnia would be required.…”
Section: T a B L E 2 Changes In Hemodynamic And Thermoregulatory Varimentioning
confidence: 99%
“…We hypothesized the effects of different knee angles and saddle height positions on skin temperature, but no differences were observed. Although changes in the saddle height can increase the neuromuscular activation of specific muscles and thus increase their heat production (Saltin et al 1970 ; Kenny et al 2003 ), these were not reflected in increased skin temperature, probably due to higher sweat rate (Buono et al 2010 ; Fujii et al 2014 ). Higher sweat rate reduces the skin temperature and this favours its thermal gradient with the core (Cuddy et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because hyperthermia-induced hyperventilation causes hypocapnia, it is plausible that the greater ventilatory sensitivity to increasing body temperature causes a greater drop in PaCO2. The results from Fujii et al 31) may therefore explain, in part, the negative relationship between ventilatory sensitivity to increasing body temperature and the cutaneous vasodilatory response.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 95%
“…3) 13) , which is consistent with the compensation hypothesis. On the other hand, Fujii et al 31) recently examined the effect of voluntary hypocapnic hyperventilation on heat-dissipating responses and reported that hypocapnia increases the Tes threshold for cutaneous vasodilation and reduces the sensitivity of the cutaneous vasodilatory response. Because hyperthermia-induced hyperventilation causes hypocapnia, it is plausible that the greater ventilatory sensitivity to increasing body temperature causes a greater drop in PaCO2.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%